2014
DOI: 10.1128/aac.00520-13
|View full text |Cite
|
Sign up to set email alerts
|

Multicenter Prospective Observational Study of the Comparative Efficacy and Safety of Vancomycin versus Teicoplanin in Patients with Health Care-Associated Methicillin-Resistant Staphylococcus aureus Bacteremia

Abstract: pThe purpose of this study was to compare the clinical efficacy and safety of vancomycin to those of teicoplanin for the treatment of adult patients with health care-associated methicillin-resistant Staphylococcus aureus (HA-MRSA) bacteremia. A multicenter observational study was prospectively conducted in 15 teaching hospitals in Korea between February 2010 and July 2011. Adult patients (>18 years old) with HA-MRSA bacteremia who were initially treated with vancomycin (VAN) (n ‫؍‬ 134) or teicoplanin (TEC) (n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
34
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(34 citation statements)
references
References 36 publications
0
34
0
Order By: Relevance
“…31,32 The addition of gentamicin and/or rifampin to vancomycin for the treatment of MRSA bacteremia and native valve endocarditis appears to offer no meaningful benefit and to confer significant risk for harm. Addition of a β-lactam antibiotic to vancomycin or daptomycin for the treatment of MRSA bacteremia is interesting but unproven.…”
Section: Discussionmentioning
confidence: 99%
“…31,32 The addition of gentamicin and/or rifampin to vancomycin for the treatment of MRSA bacteremia and native valve endocarditis appears to offer no meaningful benefit and to confer significant risk for harm. Addition of a β-lactam antibiotic to vancomycin or daptomycin for the treatment of MRSA bacteremia is interesting but unproven.…”
Section: Discussionmentioning
confidence: 99%
“…These results can be explained by inadequate dosing of teicoplanin secondary to greater protein binding compared with vancomycin. Recent data and meta-analysis suggest that teicoplanin may not be inferior to vancomycin [6]. One meta-analysis noted a lower risk of nephrotoxicity with teicoplanin than with vancomycin [5].…”
Section: Teicoplaninmentioning
confidence: 99%
“…In addition, most studies have focused on MRSA, but the role of vancomycin MIC in MSSA infection has not been fully evaluated. A number of studies, including systematic reviews and meta-analyses, have demonstrated increased mortality in the setting of SAB with vancomycin MICs of Ն2.0 g/ml (21)(22)(23)(24)(25)(26)(27)(28). Conversely, others have shown an increased risk of mortality in individuals with MICs of Ͻ2.0 g/ml (29)(30)(31)(32).…”
mentioning
confidence: 99%